2021
DOI: 10.18805/ijare.a-5804
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Severity of Alternaria Blight of Pigeonpea and its Characterisation in Northern Karnataka

Abstract: Background: The Alternaria blight of pigeonpea is considered as an important foliar disease and poses threat to the pigeonpea cultivation due to change in the climatic condition, cultivation practices and variation in pathogenic character. Though the disease is noticed in an alarming proportion after the post rainy season and causing economic yield, little is known about the severity of disease and its impact on crop production. The current study is aimed to study the disease severity and variability of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…It was found that the plant interaction towards these factors includes stimulating a group of genes that express the occurrence of biochemical and physical changes within the plant, such as strengthening the cell walls through the deposition of lignin, suberin, and callus, as well as the production of phenolic substances, phytoalexins, and the Pathogenicity Related Proteins ( PRR) that prevent and inhibit the invasion of plant pathogens [29,30]. These results are consistent with many previous studies that confirm that the different media has a direct effect on the phenotypic characteristics of the fungus A. solani and the speed of mycelium growth, As some of these studies showed that the presence of large quantities of carbon present in carbohydrates stimulates it to produce mycelium, while the lack of carbon stimulates it to produce spores [21,31,32,33].…”
Section: The Effect Culture Of Various Media On the Asolani Growth Ra...supporting
confidence: 89%
“…It was found that the plant interaction towards these factors includes stimulating a group of genes that express the occurrence of biochemical and physical changes within the plant, such as strengthening the cell walls through the deposition of lignin, suberin, and callus, as well as the production of phenolic substances, phytoalexins, and the Pathogenicity Related Proteins ( PRR) that prevent and inhibit the invasion of plant pathogens [29,30]. These results are consistent with many previous studies that confirm that the different media has a direct effect on the phenotypic characteristics of the fungus A. solani and the speed of mycelium growth, As some of these studies showed that the presence of large quantities of carbon present in carbohydrates stimulates it to produce mycelium, while the lack of carbon stimulates it to produce spores [21,31,32,33].…”
Section: The Effect Culture Of Various Media On the Asolani Growth Ra...supporting
confidence: 89%